IC 9397 Recycling In The Major Metal Industries: Trends, Developments, And Regulatory Impacts - Russell J. Foster (The National Institute for Occupational Safety and Health (NIOSH), 1994)
Public awareness of, and involvement in, recycling has increased significantly in recent years. Nevertheless, recycling is generally perceived as a new development, and is familiar only in the context of municipal solid waste management. The actual magnitude and scope of metals recycling in the United States have gone virtually unnoticed. Over time, both the quantitative and qualitative aspects of secondary metals recovery and reuse have changed substantially, while the attendant regulations have become increasingly stringent. This U.S. Bureau of Mines report examines trends and developments in major metal demand and recycling, and analyzes the possible impacts of regulations with regard to recycling activities.